Utility of a guided reading technique for cervical cancer screening. (Colombia Medica, 2006)
Background: Reading of Papanicolaou test slides follows a pattern that could omit sectors with abnormal cell nests. A low-cost guided reading strategy has been designed. Aim: To establish criteria validity and reproducibility of guided reading strategy in cervical uterine Pap smear. Methodology: To each of 300 women without cervical cancer history in order to apply Papanicolaou test, two slides were taken; both slides were read by regular method, and then reevaluated in blinded conditions with a guided technique. Diagnosis accuracy of regular and guided techniques was determined using pathologist’s reading as a gold standard. Results: When regular readings were used 65 (21.7%) of women had abnormal cytology, and 64 (21.3%) had also abnormal readings with the guided technique. Concordance of the regular reading (Kappa 0.354; 95% CI 0.250-0.457) improved with the guided technique (Kappa 0.395; 95% CI 0.285-0.505), while 24.3% slides were found abnormal in gold standard (2.7% with a high degree of malignancy). The guided reading improves all criteria validity indicators. Conclusion: This study demonstrated that the guided reading improves criteria validity indicators, correcting some technician mistakes; however, a populational study is necessary to confirm these results.